Environmental Literacy Levels of Nursing Students: A Descriptive Study - Dağal, Melike; Kılıç, Hulya Fırat (My University, 2023)
Objective: Environmental literacy is vital to form a pos- itive and close relationship between environment, education and health. This study aimed to determine the environment literacy levels of the nursing students. Material and Methods: This descriptive study was conducted on 254 undergraduate nursing students, who studied at the department of nursing at a private university in Northern Cyprus in the spring semester of the 2020-2021 academic year. Personal information form and environmental literacy scale for adults were used for data col- lection. Percentage, Kolmogorov-Smirnov test, Mann-Whitney U test and Kruskal-Wallis H test were used in the statistical analysis of the data. Results: Environmental literacy levels of the nursing students were high. Female participants had higher levels of environmental con- sciousness. Besides, environmental literacy levels of the participants, who lived for the longest time in villages, had higher levels of envi- ronmental literacy. Finally, environmental awareness levels of the par- ticipants were higher for the participants, who had higher paternal education levels and were members of environmental organizations. Conclusion: As a result, environmental literacy levels of nursing stu- dents were found to be high. Further studies on the roles and the effects of higher education institutions and environmental organizations may be conducted to improve environmental literacy among the nursing stu- dents. It is recommended that students become members of environ- mental organizations or environmental clubs at the university.
Keywords: Environment; nursing students; literacy; environmental literacy